Place-based policy in southern Italy: evidence from a dose–response approach. Issue 8 (3rd August 2021) - Cusimano, Alessandro; Mazzola, Fabio; Barde, Sylvain
ABSTRACT: This paper evaluates the effectiveness at a territorial level of a place-based policy for southern Italy, that is, territorial integrated projects (TIPs). We combine classical counterfactual designs and the construction of a dose–response function to assess the impact of the infrastructural interventions on the municipalities involved in a target region (Sicily). The results are robust enough to show policy effectiveness on both the number of workers and the number of plants. In the latter case, we also identify a significant and increasing dose–response function highlighting the positive relationship between funding intensity and the growth of plants.